Testing uncovered interest parity at short and long horizons during the post-Bretton Woods era - Chinn, Menzie David; Meredith, Guy (National Bureau of Economic Research, 2005)
"The hypothesis that interest rate differentials are unbiased predictors of future exchange rate movements has been almost universally rejected in empirical studies. In contrast to previous studies, which have used short-horizon data, we test this hypothesis using interest rates on longer-maturity bonds for the U.S., Germany, Japan and Canada. The results of these long-horizon regressions are much more positive--the coefficients on interest differentials are of the correct sign, and most are closer to the predicted value of unity than to zero. These results are robust to the use of different data frequencies, sample periods, yield definitions, and base currencies. We appeal to an econometric interpretation of the results, which focuses on the presence of simultaneity in a cointegration framework"--National Bureau of Economic Research web site.
Keywords: Ökonometrisches Modell; Foreign exchange -- Econometric models; Interest rates -- Econometric models; International finance -- Econometric models